A simulation model for evaluating the long-term financial impact of different wine grape production systems - Rabie, Pierre-Andre (Stellenbosch : Stellenbosch University, 2015)
ENGLISH ABSTRACT: Agricultural production takes place in an uncertain and complex environment, with production the result of the culmination of a variety of factors within a greater system. Consequently, accounting for the influence of variables in the production system is very difficult, making it a daunting task for decision makers to make good decisions. In the wine grape production context, this problem is accentuated due to the capital intensive and perennial nature of investments, also giving rise to a path dependency. As a result it is essential to make strategically sound decisions in order to ensure the long-term profitability and financial feasibility of wine grape production. Decision making tools, like a model, can be of invaluable support for strategic decision making. A model is used to simplify reality, by imitating and simulating the actual system as closely as possible. A simulation model was therefore developed for this thesis to be able to evaluate the long-term financial impact of different wine grape production systems and to support strategic decision making. This model can be adapted to individual farm specific features, scenarios and preferences, in the evaluation and analysis of different investment and wine grape production system decisions. For this study, the nature of agricultural systems as well as qualities required by a simulation model, were investigated. The former is followed by an investigation of the effect of the grapevine and trellis specific qualities on the possibilities of the production system, as well as the implication of capital budgeting and financing considerations on the performance of the wine grape production system. In view of the above, the model was then applied to simulate and evaluate different wine grape production systems as well as a structural transition and expansion of wine grape production, for a simulated farm in the Breedekloof region, South Africa. The model can be used for decision making and scenario planning purposes by wine grape producers and stakeholders in the wine industry.